Non-Surgical and Non-Radioiodine Techniques for Ablation of Benign Thyroid Nodules: Consensus Statement and Recommendation - Feldkamp, Joachim; Grünwald, F.; Luster, Markus; Lorenz, Kerstin; Vorländer, Christian; Führer, Dagmar (Experimental and Clinical Endocrinology & Diabetes, 2020)
Thyroid nodules and cysts are frequently diagnosed in Germany with a prevalence of about 20% in young adults reaching up to 70% in older adults. Surgery is the standard treatment of symptomatic nodules, nodules with suspicion of malignancy and thyroid cancer. Radioiodine treatment is applied for autonomously functioning nodules. During the last years new non-surgical and non-radioiodine techniques have been introduced to treat thyroid nodules. These techniques include ethanol/polidocanol treatment, radiofrequency, microwave, and laser ablation, and high frequency ultrasound ablation. A significant reduction in nodule size could be documented for these techniques in several studies, but long-term outcome data are missing. Until now, there is no general consensus regarding the appropriate indications for these methods. For this reason, the Thyroid Section (German Society for Endocrinology), the Thyroid Working Committee (German Society for Nuclear Medicine), and the German Association of Endocrine Surgeons (CAEK) for the German Society of General and Visceral Surgery (DGAV) reviewed the respective literature, discussed the pro and cons and developed a consensus statement and recommendation to help physicians and patients in their decision making.
Keywords: radiofrequency ablation; microwave ablation; laser ablation; high frequency ultrasound ablation